A 3-O-sulfated heparan sulfate dodecasaccharide (12-mer) suppresses thromboinflammation and attenuates early organ injury following trauma and hemorrhagic shock - Vidaurre, Maria del Pilar Huby; Osborn, Baron K.; Lowak, Kaylie D.; McDonald, Michelle M.; Wang, Yao-Wei W.; Pa, Veda; Richter, Jillian R.; Xu, Yongmei; Arnold, Katelyn; Liu, Jian; Cardenas, Jessica C. (Frontiers in Immunology, 2023)
Introduction: Dysregulated inflammation and coagulation are underlying mechanisms driving organ injury after trauma and hemorrhagic shock. Heparan sulfates, cell surface glycosaminoglycans abundantly expressed on the endothelial surface, regulate a variety of cellular processes. Endothelial heparan sulfate containing a rare 3-O-sulfate modification on a glucosamine residue is anticoagulant and anti-inflammatory through high-affinity antithrombin binding and sequestering of circulating damage-associated molecular pattern molecules. Our goal was to evaluate therapeutic potential of a synthetic 3-O-sulfated heparan sulfate dodecasaccharide (12-mer, or dekaparin) to attenuate thromboinflammation and prevent organ injury. Methods: Male Sprague-Dawley rats were pre-treated subcutaneously with vehicle (saline) or dekaparin (2 mg/kg) and subjected to a trauma/hemorrhagic shock model through laparotomy, gut distention, and fixed-pressure hemorrhage. Vehicle and dekaparin-treated rats were resuscitated with Lactated Ringer's solution (LR) and compared to vehicle-treated fresh-frozen-plasma-(FFP)-resuscitated rats. Serial blood samples were collected at baseline, after induction of shock, and 3 hours after fluid resuscitation to measure hemodynamic and metabolic shock indicators, inflammatory mediators, and thrombin-antithrombin complex formation. Lung and kidneys were processed for organ injury scoring and immunohistochemical analysis to quantify presence of neutrophils. Results: Induction of trauma and hemorrhagic shock resulted in significant increases in thrombin-antithrombin complex, inflammatory markers, and lung and kidney injury scores. Compared to vehicle, dekaparin treatment did not affect induction, severity, or recovery of shock as indicated by hemodynamics, metabolic indicators of shock (lactate and base excess), or metrics of bleeding, including overall blood loss, resuscitation volume, or hematocrit. While LR-vehicle-resuscitated rodents exhibited increased lung and kidney injury, administration of dekaparin significantly reduced organ injury scores and was similar to organ protection conferred by FFP resuscitation. This was associated with a significant reduction in neutrophil infiltration in lungs and kidneys and reduced lung fibrin deposition among dekaparin-treated rats compared to vehicle. No differences in organ injury, neutrophil infiltrates, or fibrin staining between dekaparin and FFP groups were observed. Finally, dekaparin treatment attenuated induction of thrombin-antithrombin complex and inflammatory mediators in plasma following trauma and hemorrhagic shock. Conclusion: Anti-thromboinflammatory properties of a synthetic 3-O-sulfated heparan sulfate 12-mer, dekaparin, could provide therapeutic benefit for mitigating organ injury following major trauma and hemorrhagic shock.